2013
DOI: 10.1038/ncb2693
|View full text |Cite
|
Sign up to set email alerts
|

F- and G-actin homeostasis regulates mechanosensitive actin nucleation by formins

Abstract: Physical force evokes rearrangement of the actin cytoskeleton. Signalling pathways such as tyrosine kinases, stretch-activated Ca(2+) channels and Rho GTPases are involved in force sensing. However, how signals are transduced to actin assembly remains obscure. Here we show mechanosensitive actin polymerization by formins (formin homology proteins). Cells overexpressing mDia1 increased the amount of F-actin on release of cell tension. Fluorescence single-molecule speckle microscopy revealed rapid induction of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 62 publications
4
85
1
Order By: Relevance
“…We find that dynamic motor activity is crucial for the stabilization of myosin at the cortex, consistent with recent work showing that myosin phosphorylation regulates contractility in epithelial morphogenesis (Kasza et al, 2014;Vasquez et al, 2014;Vasquez et al, 2016). Several actin regulators are sensitive to load, including formins (Courtemanche et al, 2013;Higashida et al, 2013;Jégou et al, 2013), and the filament-severing protein cofilin (Hayakawa et al, 2011;Tojkander et al, 2015). The mechanical dependence of myosin dynamics could thus be a result of direct effects on the motor, indirect effects on the actin filaments bound by the motor, or a combination of both.…”
Section: Results and Discussion Myosin Turnover Is Reduced Around Embsupporting
confidence: 77%
“…We find that dynamic motor activity is crucial for the stabilization of myosin at the cortex, consistent with recent work showing that myosin phosphorylation regulates contractility in epithelial morphogenesis (Kasza et al, 2014;Vasquez et al, 2014;Vasquez et al, 2016). Several actin regulators are sensitive to load, including formins (Courtemanche et al, 2013;Higashida et al, 2013;Jégou et al, 2013), and the filament-severing protein cofilin (Hayakawa et al, 2011;Tojkander et al, 2015). The mechanical dependence of myosin dynamics could thus be a result of direct effects on the motor, indirect effects on the actin filaments bound by the motor, or a combination of both.…”
Section: Results and Discussion Myosin Turnover Is Reduced Around Embsupporting
confidence: 77%
“…Neither myosin IIA nor myosin IIB was found to be associated with the perinuclear actin rim, and inhibition of myosin II contractility did not affect formation of this actin structure. Although various studies have reported observations of actin reorganization on mechanical stimuli (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(14)(15)(16)(17), the transient perinuclear actin polymerization is revealed here for the first time to our knowledge.…”
Section: Discussionmentioning
confidence: 78%
“…Fluid shear stress, for example, induces actin stress fiber assembly and realignment along the direction of flow (1)(2)(3)(4), whereas the cyclic stretch of an elastic substrate induces a reorientation of stress fibers under some angle to the direction of stretch (5)(6)(7)(8). Applying mechanical force to cells by a microneedle results in focal adhesion growth and activation of formin-type actin nucleators (9,10). Similarly, local application of force through fibronectin or collagen-coated beads trapped by optical or magnetic tweezers leads to the local reorganization of the actin cytoskeleton.…”
mentioning
confidence: 99%
“…Because INF2 plays a role in mitochondrial dynamics (17) and because mitochondria play central roles in cellular homeostasis (37,38), such a mechanism could be a means for monitoring cellular state. Interestingly, the activity of mDia1 is also increased by increases in actin monomer concentration (35,39), but the mechanism of this effect appears different from that of INF2 because this effect does not require DID or DAD regions.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the cytoplasmic concentrations of actin, profilin, and thymosin ␤4 (a sequestering protein whose actin monomer binding site overlaps that of INF2-DAD), the concentration of free actin monomer is estimated to be in the micromolar range in mammalian cells (34,35). Fluctuations in cellular actin polymerization, increasing or decreasing the free monomer pool, could conceivably increase or decrease INF2 activity, similar (but in an opposite manner) to models of serum response factor-negative regulation by actin monomer levels (36).…”
Section: Discussionmentioning
confidence: 99%